1990
DOI: 10.1007/bf01963642
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter jejuni infection occurring during pregnancy

Abstract: Campylobacter infections occurring during pregnancy have been associated with spontaneous abortion, stillbirth, prematurity and neonatal sepsis, all ten Campylobacter jejuni infections diagnosed in the approximately 24,000 pregnant women attending a 520-bed hospital between January 1984 and December 1988 were reviewed. Nine women delivered healthy babies at term. In one case, Campylobacter infection at 28 weeks of gestation was associated with premature labour and delivery with subsequent neonatal sepsis and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 7 publications
0
7
0
2
Order By: Relevance
“…This statement is difficult to verify because data on the incidence of abortion caused by other microorganisms are lacking or are not directly comparable. For example, Campylobacter species, like Brucella species, are welldescribed causes of abortion in animals; however, in a series of 10 pregnant women with Campylobacter jejuni infection who were at a single hospital, only 1 (10%) had premature labor at 28 weeks' gestation that resulted in a neonatal death [18]. Other reports of Campylobacter infection in pregnant women include a report of a series of cases that were selected on the basis of the occurrence of abortion [19] and single case reports of fetal loss in association with septic shock, bacteremia, and diarrheal illness [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…This statement is difficult to verify because data on the incidence of abortion caused by other microorganisms are lacking or are not directly comparable. For example, Campylobacter species, like Brucella species, are welldescribed causes of abortion in animals; however, in a series of 10 pregnant women with Campylobacter jejuni infection who were at a single hospital, only 1 (10%) had premature labor at 28 weeks' gestation that resulted in a neonatal death [18]. Other reports of Campylobacter infection in pregnant women include a report of a series of cases that were selected on the basis of the occurrence of abortion [19] and single case reports of fetal loss in association with septic shock, bacteremia, and diarrheal illness [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Maternal C. jejuni bacteremia is associated with fetoplacental involvement, resulting in premature labor, perinatal sepsis, and neonatal meningitis. Fetal and neonatal mortality rate may be as high as 80%, particularly if infection occurs before the third trimester of pregnancy (104,105). Other extraintestinal manifestations (Table 2) are rare.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…12 Campylobacter is responsible for pancreatitis, cholecystitis, cystitis, Guillain-Barre syndrome and even miscarriage. 13,14 We have previously shown that intraperitoneal inoculation of C. jejuni in mice, in spite of no visible signs of illness, resulted in bacterial dissemination and tissue invasion. 15 Mice intraperitoneally injected with L. monocytogenes exhibited some generalized symptoms (inactivity, ruffled fur) and more prominent gross and histologic abnormalities in the examined organs.…”
Section: Introductionmentioning
confidence: 99%